The use of Moringa oleifera Extract in the Treatment and Control of Intestinal Coccidiosis in Weaned Rabbit - Elbarbary , Noha B.; Saleh, Gehan K.; Ali, Hanaa S.; Abd EL Maged, Rehab R. (Journal of Advanced Veterinary Research, 2023)
This study aimed to introduce some natural alternatives that can be used in the treatment and control of coccidiosis in weaned rabbits. Moringa oleifera (M. oleifera) was used for its immune enhancer effect and its content of antioxidant bioactive compounds. In the current investigation, sixty domestic male rabbits were divided into six groups with 10 rabbits in each. Group 1 (G1): noninfected and non-treated group; G2 was noninfected and supplemented with M. oleifera extract in drinking water at 1.5 g/L; G3 was infected and non-treated (control positive); G4 was supplemented with M. oleifera extract in drinking water (1.5 g/L) one week before the experimental infection till the end of the experiment; G5 was infected and treated by M. oleifera extract in drinking water (1.5 g/L) at the 5th-day post-inoculation till the end of the experiment; G6 was infected and treated with amprolium 20% (1.2 g/L) at the 5th-day post-inoculation for five successive days. Rabbits were infected by a suspension containing 104 sporulated oocysts of Eimeria magna, E. media, and E. perforans. G3 exhibited the typical symptoms of coccidiosis with a mortality rate of 30%, while clinical signs in G4, G5, and G6 were lesser than in G3 with a mortality rate of 0%. There was a significant increase in body weight and a significant decrease in oocyst count in G4, G5, and G6 compared with G3. In Addition, a significant decrease (p>0.05) in the liver enzyme (ALT), A/G ratio, serum cholesterol, and triglycerides, with a significant increase (p>0.05) in serum total protein activities in the treated groups (G4, G5, and G6) compared to the control positive group. Serum AST, creatinine, and urea did not report any changes among treatments, and they were within the normal range. While antioxidant activities in tissue showed a significant reduction in the malondialdehyde (MDA), a significant increase in SOD (superoxide dismutase), and GSH (glutathione reduced) activities in the treated groups compared to the control positive group. Histopathological changes of the intestine showed better profiles in the supplemented groups. Besides, histopathological changes in the intestine and the microscopical lesion score were significantly reduced in the challenged groups supplemented and treated with M. oleifera and amprolium. In conclusion, M. oleifera could be effective in controlling rabbit coccidiosis. Â 